Conservation Strategies for Railway Heritage of Cyprus - Mısırlısoy, Damla; Günçe, Kağan (ICONARCH International Congress of Architecture and Planning, 2017)
Industrial heritage buildings and structures should be conserved and sustained for further generations as well as other heritage buildings since they are crucial in terms of collective memory and sense of the continuity. The research is conducted to develop conservation and reuse strategies for the railway stations, which were built in 1905 in Cyprus when the island was under British rule. Heavy wartime usage, lack of investment in the railway, plus increasing competition from road transport had been caused the number of passengers to decrease. Then, the railways were closed in 1951 and are not in use today. The railway buildings and structures are important in terms of the cultural heritage of the Island for both communities. Between 1905 and 1951 there was a railway line on the island and still, there is no active railway route neither in the Northern nor Southern part of the island. The traces of the railway heritage are about to disappeared. In time, exploration of the traces of the former line is getting hard since it spans the two zones of Cyprus. In this respect, the railway buildings and structures need to be studied and preserved within the context of the industrial heritage of the island. Unfortunately, most of these heritage structures were abandoned without any maintenance, not listed or properly reused. There is no enough attention on the issue and no research has been done in terms of identification and conservation of the railway heritage so far. In this respect, the aim of this research is to identify and document the former railway stations that still exists today as a first step and then, to develop conservation and reuse proposals by focusing on their urban, contextual, socio-cultural and economic values for both communities. Firstly, with the help of historic documents and archives, a list of railway stations that were built in British Colonial period in Cyprus has been identified. Then, observations through site survey have been done for the identification of the former station buildings that still exists today. As a result of the field survey, 10 railway stations were identified that is worth for being preserved as a part of the Island’s industrial heritage. Conservation problems of the railway heritage buildings have been identified and reuse proposals have been developed according to the mentioned heritage values and the needs of their districts. The railway heritage buildings and structures should not be preserved only physically, but also the memory of the place should be sustained that defines identity of communities and makes the places meaningful.